Environmental Factors that Shape the Behavior of White Rhinoceros in a Captive Setting in Yunnan, China - Zhang, Yuchen (International Journal of Natural Resources and Environmental Studies, 2025)
Understanding the determinants of rhinoceros behavior is important in field and enclosure management, particularly during global climate change. In this study, the influence of five central environmental parameters (ambient temperature, relative humidity, temperature–humidity index (THI), light intensity, and wind speed behavior) on white rhinoceros (Ceratotherium simum) behavior was examined in captivity in Yunnan, China. Special attention was given to the rhino behavior walking, given it was the most frequently reported active behavior (e.g. excluding resting) and because this activity shapes intra and interspecific interactions and carries high energy costs. Results show there to be a highly significant positive relationship between THI and walking duration, while wind speed and light intensity contributed relatively weakly. The findings stress the importance of thermal environment in shaping locomotor activity. While future research is required to extrapolate these findings to more extensive populations and to understand the influence of seasonality on rhino behavior, this study presents the valuable quantitative evidence on environmental determinants of captive white rhinoceros behavior in China and offers guidance for future husbandry, welfare assessment, and restoration planning.